Investigação das propriedades biocidas de nanopartículas de prata preparadas em meio de citrato de sódio - RODRIGUES, Isabela Fernandes (2017)
Silver nanoparticles have a high area/volume ratio, therefore their antimocrobial property is greatly increased. They exhibit action against a wide range of pathogenic microorganisms such as gram negative and gram positive bacteria, algae and fungi. Silver ions can be reduced by a wide range of organic substances such as alcohols, carbohydrates, tartaric acid, ascorbic acid, etc. Synthesis of the nanoparticles was carried out using sodium citrate as reducing agent in the presence of the sodium dodecylsulfate. Characterization of silver nanoparticles was performed by UV-Vis spectroscopy, where it was obtained nanoparticles with diameter of 10-50 nm. A factorial design of 2³ was done using as variables the reagent concentrations and the surface plasmon absorption spectra of silver nanoparticles. Through response surfaces a relationship was obtained between the reagents concentrations and the nanoparticles sizes. The size of the nanoparticles directly influence their biocidal properties, therefore, nanoparticles in the range of 10-14 nm were used on Candida albicans. In this way, the toxicity of silver suspensions and silver encapsulated by liposomes as carriers in plankton and biofilm medium was evaluated. It was concluded that the silver nanoparticles in their different microforms (suspension and liposome) presented activity on C. albicans in both planktonic and biofilm environments.